Effects of a Multicomponent Cognitive Stimulation Program on Cognitive Function Improvement Among Elderly Women - Jeong-Mo Park; Mi-Won Kim; Hee-Young Shim (Elsevier, 2019)
Purpose: This study was conducted to identify the effect of a multicomponent cognitive stimulation program (MCSP) on the improvement of older people's cognitive abilities. It also aimed to determine whether the effectiveness of the MCSP is related to age. Methods: A one-group pretest-posttest design was used. The program was conducted once a week for 10 weeks. The Korean-Montreal Cognitive Assessment (K-MoCA) was used to measure cognitive functions before and after the MCSP. Participants included 37 people aged over 65 years with normal cognitive functions and living in I city. A paired t-test was used to compare K-MoCA scores before and after the MCSP, and a two-way analysis of variance was performed to confirm whether there is an interaction between the MCSP and age. Results: It was found that the MCSP had a significant effect on improving cognitive functions (t = −5.15, p < .001). Regarding the subdomains, visuospatial/executive ability, recall, naming, and language ability showed significant effects; however, abstractive ability-which was not a focus of the program-showed no significant effect. There were differences in visuospatial/executive functions, language skills, and memory between the 65-79 years age group and the aged over 80 group. Further, regarding the relationship between the MCSP and age, it was found that their interaction was significant only with regard to visuospatial/executive ability. Conclusion: The MCSP helps to improve the cognitive functions of the elderly; however, its effect differs between the young-old group and the old-old group. Therefore, age should be considered when developing MCSPs. Keywords: aged, aging, cognition, cognitive behavioral therapy, mental status and dementia tests